Involvement of SLC39A6 in gastric adenocarcinoma and correlation of the SLC39A6 polymorphism rs1050631 with clinical outcomes after resection - Gao, Jian (BMC Cancer, 2019)
BACKGROUND: The single-nucleotide polymorphism SLC39A6 rs1050631 is strongly implicated in esophageal squamous cell carcinoma, leading us to question whether it may also play a role in gastric adenocarcima (GA). METHODS: We genotyped the SLC39A6 rs1050631 in 512 patients who underwent GA resection. All study subjects lived in an area of China with high GA incidence. Genotypes were examined for possible correlation with survival and recurrence. The potential involvement of SLC39A6 in gastric cancer was explored in clinical samples and cell culture studies. RESULTS: Multivariable analysis showed that patients with the CT + TT genotype at SLC39A6 rs1050631 were at greater risk of recurrence (hazard ratio, HR 1.387, p = 0.004) and death (HR 1.429, p = 0.002) than patients with CC genotype. Median recurrence-free and overall survival were significantly shorter in patients with the CT + TT genotype (20, 27 months) than in patients with the CC genotype (36, 43 months, p = 0.001, p < 0.001). Patients with the CT + TT genotype who were male or ≥ 60 years, or who had a tumor ≥5 cm or a moderately differentiated tumor were at significantly higher risk of recurrence and death. SLC39A6 was overexpressed in tissues from GA patients and in GA cell lines, and SLC39A6 knockdown in GA cell lines inhibited their proliferation, migration and invasion. CONCLUSION: SLC39A6 rs1050631 correlates with post-resection prognosis of GA patients and SLC39A6 may participate in GA onset or progression.